Pengembangan Insrumen Assertiveness Siswa Sekolah Menengah Atas (SMA): Analisis Model Rasch - Raisa, Zarul; Suherman, Suherman; Yudha, Eka Sakti; Muhammad, Fadhil (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
His study aimed to develop an instrument that will be used to measure the assertiveness of senior high school students. This quantitative study involved 300 senior high school students in Aceh. Based on an analysis of the relevant literature, this study developed 38 items that collectively described assertiveness. Data was collected using a assertiveness scale and analyzed using the Rasch model. The results show that 1) Cronbach's alpha value is 0.83 which means the interaction between item and person is in the very good category, 2) the item reliability coefficient is 0.99 where the item belongs to the special category, and 3) the person reliability coefficient is 0.83 which means that students respond consistently to each item. Based on the results above, we can see that 37 valid items and the other is invalid. Overall, it can be concluded that the assertiveness scale has good psychometric properties, and it can be used by counselors or counseling guidance teachers to measure students' assertiveness.